P04 Rct of a motivational lifestyle intervention (the healthy eating and lifestyle programme (help)) for obese young people. (27th April 2015) - Christie, D; Hudson, L; Costa, S; Mathiot, A; Holt, R; Kinra, S; Kessel, A; Wong, ICK; Cole, TJ; Morris, S; Nazareth, I; Viner, RM
Abstract : Aims: To assess whether a motivational multi-component lifestyle intervention delivered in the community was effective in reducing body mass index (BMI) and improving related health outcomes in obese adolescents. Methods: 174 obese adolescents (13–17 years old; 109 females) from a UK community setting were randomised into intervention or control arms. Intervention participants received 12 sessions across 6 months, addressing lifestyle behaviours and focusing on motivation to change and self-esteem rather than weight change. The intervention was delivered by trained Graduate Health Workers in community settings. Control participants received a single 2 h nurse-delivered session providing didactic weight management advice. The primary outcome was BMI change at 6 months. Secondary outcomes included body fat (impedance;), dieting behaviours, self-esteem and quality of life. Random-effects linear regression was used to detect differences in end-point outcomes between Intervention and control groups, adjusting for sex, age, and outcome value at the beginning of the intervention. The primary analyses used the intention to treat sample. Results: 145 (83.3%) adolescents completed the intervention. Mean BMI across the whole group was 32.3 kg/m 2 (SD 4.4) at start and 32.6 kg/m 2 (SD 4.7) at the end of the intervention. We found no significant difference in the primary outcome (BMI) at 6 months: effect estimate -0.06 (95% CI: -0.57 to 0.45) p = 0.8). No significant differences were observed for changes in secondary outcomes (all p > 0.4) between intervention and control groups at 6 months. Fidelity monitoring showed moderately strong fidelity to treatment. The process evaluation found that participants and their families found the intervention highly engaging, respectful and helpful in making behavioural changes. Discussion: We did not find evidence that a motivational multi-component lifestyle modification intervention delivered in the community was effective in reducing BMI or improving health and well-being in a community sample of obese adolescents, despite moderately strong fidelity and process evidence that young people used the intervention to make changes in their lifestyle. Our findings suggest that obesity interventions with a strong theoretical basis and evidence of effectiveness when delivered by trained psychologists may not be effective when delivered at lower intensity in the community by entry-level health workers.